A catalogue of Indian Stathmopodidae (Lepidoptera: Gelechioidea) - Sahoo, Kishore Chandra (Zootaxa, 2025)
This study presents a comprehensive catalogue of the family Stathmopodidae (Lepidoptera: Gelechioidea) known from India. A total of 53 species belonging to 10 genera are documented, along with information on their type localities, type depositories, distribution, host plants, and references to illustrations, where available. The subfamily Stathmopodinae is the most diverse, comprising 5 genera and 43 species known from India. The genus Stathmopoda is the most speciose with 31 Indian species. Meghalaya state has the highest diversity with 6 genera and 19 species recorded. Host information is known for 19 Indian species, with most feeding on various plant species, and others feeding on soft bodied insects or dried products.